Membrane insertion mechanism and molecular assembly of the bacteriophage lysis toxin ΦX174‐E. (12th December 2020) - Mezhyrova, Julija; Martin, Janosch; Peetz, Oliver; Dötsch, Volker; Morgner, Nina; Ma, Yi; Bernhard, Frank
Abstract : The bacteriophage ΦX174 causes large pore formation in Escherichia coli and related bacteria. Lysis is mediated by the small membrane‐bound toxin ΦX174‐E, which is composed of a transmembrane domain and a soluble domain. The toxin requires activation by the bacterial chaperone SlyD and inhibits the cell wall precursor forming enzyme MraY. Bacterial cell wall biosynthesis is an important target for antibiotics; therefore, knowledge of molecular details in the ΦX174‐E lysis pathway could help to identify new mechanisms and sites of action. In this study, cell‐free expression and nanoparticle technology were combined to avoid toxic effects upon ΦX174‐E synthesis, resulting in the efficient production of a functional full‐length toxin and engineered derivatives. Pre‐assembled nanodiscs were used to study ΦX174‐E function in defined lipid environments and to analyze its membrane insertion mechanisms. The conformation of the soluble domain of ΦX174‐E was identified as a central trigger for membrane insertion, as well as for the oligomeric assembly of the toxin. Stable complex formation of the soluble domain with SlyD is essential to keep nascent ΦX174‐E in a conformation competent for membrane insertion. Once inserted into the membrane, ΦX174‐E assembles into high‐order complexes via its transmembrane domain and oligomerization depends on the presence of an essential proline residue at position 21. The data presented here support a model where an initial contact of the nascent ΦX174‐E transmembrane domain with the peptidyl‐prolyl isomerase domain of SlyD is essential to allow a subsequent stable interaction of SlyD with the ΦX174‐E soluble domain for the generation of a membrane insertion competent toxin. Abstract : Due to high toxicity in a wide range of Gram‐negative bacteria phage, ΦX174 is particularly interesting for medical applications. Our data support a revised two‐step activation model of the phage toxin ΦX174‐E by the bacterial chaperone SlyD. Sequential binding of SlyD to both ΦX174‐E domains prevents formation of an inactive conformation and catalyzes its membrane insertion. Within the membrane, ΦX174‐E forms oligomeric complexes, a potential prerequisite for lysis.